Desain Aplikasi AMAN : Aplikasi Keselamatan untuk Wanita dan Anak – Anak Berbasis Mobile - Alvin Wiraprathama; I Made Widiartha (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
Crime is one of the biggest threat and still often occurs easily in daily life in Indonesia until today. According to BPS ( Badan Pusat Statistik ) Indonesia, there are more than 200.000+ crime cases that happened every year. Crime can happen to anyone especially to women and children. This study aim to help solving women and children safety problem by taking the advantage of daily use of mobile phone and smart gadget. In order to solve the problem, the author create a design solution using prototyping method and model it in the form of a mobile application. In the prototype, user can send emergency request at anytime they need, call emergency contact or nearby authorities to help them. Hopefully this application can reduce the crime number and make a safer environment for women and children.